Історична географія Скитії у німецькій історіографії XIX ст. - Трубчанінов, С. (Історико-географічні дослідження в Україні, 2023)
У багатьох роботах німецьких учених XIX ст. піднімалися питання історичної географії Скитії. Однак, дана проблематика ще не стала предметом спеціального історіографічного дослідження німецьких чи українських науковців. Метою даної розвідки є вивчення уявлень у німецькій науковій думці XIX ст. про межі та територію Скитії, походження і розселення племен скитів та їхніх сусідів, зв’язки колоній еллінів у Надчорномор’ї зі скитами та ін. ﻿Історіографічних розвідок, дотичних темі дослідження, небагато. Серед них слід виділити праці Олександра Домбровського, Алєксандри Нейхардт, Арістіда Доватура та Дмітрія Каллістова, які з’явилися друком у 1980-х рр. Наголошується, що більшість німецьких дослідників XIX ст. вважало інформацію Геродота про Скитію достатньо повною, проте учені вказували і на окремі помилки «батька історії». Авторами німецьких/німецькомовних робіт з історичної географії Скитії були відомі географи (Конрад Маннерт, Фрідріх Август Укерт та Карл Ріттер), історики (Арнольд Геєрен, Бартольд Георг Нібур та ін.), філологи (Фрідріх Бергманн, Каспар Цойсс та ін.). Також виходили розвідки викладачів гімназій, які переважно публікувалися в навчально-методичних виданнях окремих навчальних закладів (Карл Струве, Георг Майр, Пантелеймон Клим та ін.). Вчені висловлювали різні гіпотези щодо етнічної приналежності скитів та інших племен Скитії. Розроблена Б.Г. Нібуром теорія про приналежність скитів до монголів мала чимало прихильників у першій половині – середині XIX ст. (Август Гансен, Карл Нойманн та ін.). Учений-енциклопедист Едуард Ейхвальд у своїх працях 1830-х рр. доводив, що скити були племенами фінського походження, які колись мешкали на схід від Уральських гір. На його думку, савромати, неври, будини, даки і гети були слов’янами. У той же час, відомий німецький історик і філолог Каспар Цойсс відносив скитсько-сарматські племена до іранців. Відомий публіцист Фрідріх Людвіг Лінднер пропагував теорію про слов’янство скитів і сарматів, яка була популярною серед російських авторів у XVIII – на початку XIX ст. Сумнівну з наукового погляду теорію про етногенетичний зв’язок між скитами і німцями поширювали Фрідріх Бергманн та Йоганнес Фресль. There is noted in the article that issues of the historical geography of Scythia were raised in many works of German scientists of the 19th century. However, this issue has not yet become the subject of a special historiographical study by German or Ukrainian scientists. The purpose of this research is to study ideas about the boundaries and territory of Scythia, the origin and settlement of the Scythian tribes and their neighbors, the connections of the Hellenic colonies in the Black Sea with the Scythians, and other in German scientific thought of the 19th century. There are few historiographic studies being related to the topic of research. Among them there should be singled out the works of Oleksandr Dombrovskyi, Aleksandra Neyhardt, Aristid Dovatur, and Dmitrii Kallistov, which were printed in the 1980s. It is emphasized that most German researchers of the 19th century considered Herodotus’ information about Scythia to be sufficiently complete, but scholars also pointed out certain mistakes of the “father of history.” The authors of German/German-language works on the historical geography of Scythia were famous geographers (e.g., Konrad Mannert, Friedrich August Ukert and Karl Ritter), historians (e.g., Arnold Hermann Ludwig Heeren, Barthold Georg Niebuhr, and etc.), and linguists (e.g., Friedrich Wilhelm Bergmann, Johann Kaspar Zeuss, and etc.). In addition, there were published scientific papers of gymnasium teachers, which were mainly included in educational and methodical editions of individual gymnasiums (e.g., Karl Ludwig Struve, Georg Mayr, Pantelimon Klym, etc.). Scientists expressed various hypotheses regarding the ethnicity of the Scythians and other tribes of Scythia. The theory about the affiliation of the Scythians to the Mongols developed by Barthold Georg Niebuhr had many supporters in the first halfmiddle of the 19th century (e.g., August Heinrich Hansen, Karl Johann Heinrich Neumann, etc.). The scientist and encyclopedist Johann Karl Eduard Eichwald in his writings of the 1830s argued that the Scythians were tribes of Finnish origin who once lived east of the Ural Mountains. In his opinion, the Sauromatians, the Nevri, the Budins, the Dacians, and the Getae were Slavs. At the same time, the famous German historian and linguist Johann Kaspar Zeuss attributed the Scythian-Sarmatian tribes to the Iranians. The famous publicist Friedrich Ludwig Lindner promoted the theory of the Scythians and Sarmatians Slavic origin, which was popular among Russian authors in the 18th and early 19th centuries. The scientifically dubious theory about the ethnogenetic connection between the Scythians and the Germans was propagated by Friedrich Wilhelm Bergmann and Johannes Fressl. In conclusion, German scientists of the 19th century analyzed the evidence of Herodotus and other authors about Scythia (its borders, territory, climate, population, etc.) and formulated various theories regarding the ethnicity of the Scythians.